Pemberdayaan Mustahik melalui Zakat Komunitas: Studi Kasus BAZNAS Kabupaten Bangkalan dan Kota Surabaya perspektif Teori Kesejahteraan Jamaluddin Athiyyah - Sari, Nurita; Nurhayati, Nurhayati; Mustofa, Mustofa; Suis, Suis (Maliyah : Jurnal Hukum Bisnis Islam, 2025)
Abstract: This research aims to analyze the mustahik (zakat recipients) This research aims to analyze the empowerment model for mustahik (zakat recipients) through Community Zakat at the National Zakat Agency (BAZNAS) of East Java Province, with case studies at BAZNAS of Bangkalan Regency and BAZNAS of Surabaya City. Specifically, this study examines the implementation of the empowerment model, its relevance to Jamaluddin Athiyyah's welfare theory perspective, and its impact on the welfare of mustahik. The background for this research is the significant potential of zakat in Indonesia, particularly in East Java, and the strategic role of BAZNAS in its management. The research method employed is qualitative with a descriptive approach. Data collection techniques included documentation and interviews, with data validity tested through source and technical triangulation. Data analysis was conducted through data reduction, data display, and conclusion drawing. The research findings indicate that the empowerment models implemented at BAZNAS of Bangkalan Regency and BAZNAS of Surabaya City are adapted to the respective local needs of each area. Empowerment strategies encompass skills training, business capital assistance, and community strengthening. From the perspective of Jamaluddin Athiyyah's welfare theory, especially in the economic field, this program aligns with the principles of Islamic welfare, which include the fulfillment of basic needs, the strengthening of social solidarity, and individual empowerment. This community zakat program has been proven to contribute to improving the welfare and economic independence of mustahik, as evidenced by the increase in their income. Nevertheless, some challenges were identified related to the amanah (trustworthiness/accountability) of mustahik in managing the aid. Keywords: Mustahik Empowerment, Community Zakat, Jamaluddin Athiyyah's Welfare Theory. Abstrak: Penelitian ini bertujuan untuk menganalisis model pemberdayaan mustahik melalui Komunitas Zakat pada BAZNAS Provinsi Jawa Timur, dengan studi kasus di BAZNAS Kabupaten Bangkalan dan BAZNAS Kota Surabaya. Secara spesifik, penelitian ini mengkaji implementasi model pemberdayaan, relevansinya dengan perspektif teori kesejahteraan Jamaluddin Athiyyah, serta dampaknya terhadap kesejahteraan mustahik. Latar belakang penelitian ini adalah potensi besar zakat di Indonesia, khususnya di Jawa Timur, dan peran strategis BAZNAS dalam pengelolaannya. Metode penelitian yang digunakan adalah kualitatif dengan pendekatan deskriptif. Teknik pengumpulan data meliputi dokumentasi dan wawancara, dengan validitas data diuji melalui triangulasi sumber dan teknik. Analisis data dilakukan melalui reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa model pemberdayaan yang diterapkan di BAZNAS Kabupaten Bangkalan dan BAZNAS Kota Surabaya disesuaikan dengan kebutuhan lokal masing-masing daerah. Strategi pemberdayaan mencakup pelatihan keterampilan, bantuan modal usaha, dan penguatan komunitas. Dari perspektif teori kesejahteraan Jamaluddin Athiyyah, khususnya dalam bidang ekonomi, program ini sejalan dengan prinsip kesejahteraan Islam yang meliputi pemenuhan kebutuhan dasar, penguatan solidaritas sosial, dan pemberdayaan individu. Program zakat komunitas ini terbukti berkontribusi dalam meningkatkan kesejahteraan dan kemandirian ekonomi mustahik, terlihat dari peningkatan pendapatan mereka. Meskipun demikian, ditemukan beberapa tantangan terkait amanah mustahik dalam pengelolaan bantuan. Kata Kunci: Pemberdayaan Mustahik, Zakat Komunitas, Teori Kesejahteraan Jamaluddin Athiyyah.